Disruption of cardiac bioelectrical activity after intrauterine hypoxia and approaches to cardioprotection in the postnatal period - Popazova, O. O.; Попазова, Олена Олександрівна (Запорізький державний медико-фармацевтичний університет, 2024)
Purpose of the study: to assess the cardioprotective effects of medications that alter the NO system on the electrocardiogram (ECG) of rats that are two months old following prenatal hypoxia.
Keywords: тези доповідей